A Study on the Effect of Work Culture, Employee Empowerment, Librarianship Training and Work Ethics on Employee Performance at National Library of Indonesia - Masykuri, Ahmad; Tippe, Syarifudin; Akbar, Maruf (International Journal of Scientific Research and Management (IJSRM), 2020)
This is a study on the effect of work culture, employee empowerment, librarianship training and work ethics on employee performance at National Library of Indonesia in Jakarta, Bung Karno Library in Blitar, and Bung Hatta Library in Bukit Tinggi. This was a quantitative research using path analysis. The sampling technique is simple random sampling and a representative samples of 124 librarians. The data were collected using a Likert-type structured questionaire and the validity was tested using the Pearson Product Moment test analysis and Reliability test using Cronbach Alpha test. The result showed that (1) Work culture, employee empowerment, librarianship training and work ethic have direct positive effects on performance; 2. Work culture and employee empowerment have direct positive effects on work ethic; and 3. Employee empowerment has no direct positive effects on work ethics. The study also shows the importance of policy and chief regulation to strengthen the work culture, librarians’ empowerment equaty, and enhancement librarianship training.